Analisis Pengaruh Harga, Kualitas Jasa, dan Promosi terhadap Kepuasan Pelanggan dalam Menggunakan Jasa Laundry (Studi Kasus pada Laundry Kilat Pak Edy di Bandar Lampung) - Alfi, Dava Arifta; Barusman, Andoni Fornio (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to examine the effect of price, service quality, and promotion on customer satisfaction at Pak Edy's Express Laundry. Primary data were collected through interviews and questionnaires distributed to all customers of Pak Edy's Express Laundry. A purposive sampling technique was used to obtain a sample of 100 respondents. Descriptive analysis and multiple linear regression were conducted using SPSS 26 software. The results showed that price, service quality, and promotion positively affect customer satisfaction both partially and simultaneously. The service quality variable has the most significant impact on customer satisfaction compared to the other variables. This indicates that enhancing service quality can substantially increase customer satisfaction.